2020 IEEE International Conference on Systems, Man, and Cybernetics (SMC) 2020
DOI: 10.1109/smc42975.2020.9283335
|View full text |Cite
|
Sign up to set email alerts
|

Bone Feature Segmentation in Ultrasound Spine Image with Robustness to Speckle and Regular Occlusion Noise

Abstract: 3D ultrasound imaging shows great promise for scoliosis diagnosis thanks to its low-costing, radiation-free and realtime characteristics. The key to accessing scoliosis by ultrasound imaging is to accurately segment the bone area and measure the scoliosis degree based on the symmetry of the bone features. The ultrasound images tend to contain many speckles and regular occlusion noise which is difficult, tedious and time-consuming for experts to find out the bony feature. In this paper, we propose a robust bone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
0
3
0
Order By: Relevance
“…The most-used method is the U-Net. Huang, Z. et al [97] introduced a segmentation method called RSN-U-net, as shown in Figure 8. Aiming at the spot and regular occlusion noise that are prone to appear in ultrasound medical images, this method uses total variance (TV) loss to train the neural network and successfully improves the robustness of spot and regular occlusion noise, effectively segmenting the bone features in ultrasound spine images.…”
Section: Machine Learning Methods For 3d Imagementioning
confidence: 99%
“…The most-used method is the U-Net. Huang, Z. et al [97] introduced a segmentation method called RSN-U-net, as shown in Figure 8. Aiming at the spot and regular occlusion noise that are prone to appear in ultrasound medical images, this method uses total variance (TV) loss to train the neural network and successfully improves the robustness of spot and regular occlusion noise, effectively segmenting the bone features in ultrasound spine images.…”
Section: Machine Learning Methods For 3d Imagementioning
confidence: 99%
“…Subsequent publications introduce extensions like the 3D U-Net [30], the U-Net++ with redesigned skip connections [31] or the nnU-Net framework for automated configuration of architecture and training process [32]. Most works on bone segmentation in US images rely on the original U-Net [33][34][35][36][37][38][39][40][41][42] as well as the U-Net++ [43]. Several works introduce drop-out during inference [44,45] or training [46] to incorporate segmentation uncertainty.…”
Section: A Us Image Segmentationmentioning
confidence: 99%
“…Different related results have been obtained. Huang et al [23] proposed an efficient regularization-based algorithm to address the occlusion issue in VPI images for enhanced spine segmentation. Zhao et al [24] proposed to introduce the structure supervision to the representation learning in a self-attention manner for more effective spine segmentation.…”
Section: B Scoliosis Diagnosis With Ultrasoundmentioning
confidence: 99%